The impact of environmental management practices in KwaZulu Natal, South Africa - Madikizela, Zolisa (University of the Witwatersrand, Johannesburg, 2022)
The research study appraises the effectiveness of the environmental management practices deployed at the Umbogintwini Industrial Complex (UIC) to manage historic and present environmental pollution that is the result of industrial activities over the past 100 years. The study was conducted at the African Explosives and Chemical Industries (AECI) site in the UIC located approximately 25 kilometres (km) south of Durban in KwaZulu Natal (KZN). In the UIC, AECI, its subsidiaries, and other businesses leasing property inside the UIC (tenants) have manufactured, stored, and supplied a wide range of industrial chemicals since 1907. The study uses a qualitative case study research methodology and explores the views of internal stakeholder i.e. AECI employees and external stakeholders’ i.e. tenants and other stakeholders regarding the effectiveness of environmental management practices deployed on site. A total of 25 participants were interviewed for this study. The interviews were done in person and some Via Teams Meetings. The theoretical and conceptual lenses that the study used include the concept of sustainability, green manufacturing, resource-based view theory and institutional theory. The overall findings of this study revealed that AECI personnel, Consultants and Regulators that are involved in the implementation of environmental management practices are aware of the environmental management practices and strongly committed to implement the practices, while the NPOs and communities around the site are wanting in environmental awareness. The study also shows that AECI’s environmental practices are not sufficiently recorded, making it harder to track and improve on them in the long run. As a result, the study proposes that the AECI should build a secure digital data management system that will aid in the keeping of records, the analysis of data, the creation of follow-up schedules, and the flagging of non- compliance, among other things. Moreover, the findings of this study support the value of sustainable development and green manufacturing as a means of investigating how environmental management practices can be implemented effectively in South Africa’s industrial complexes as this is the key finding that distinguishes the UIC. Furthermore, this study recommends that future studies assess the environmental management techniques used at other industrial complexes in South Africa or other 5 developing countries to assess the sustainability of the current plans, relating them to green manufacturing in order to stimulate continuous development.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, 2022
Keywords: Environmental Management; Internal and External Stakeholders; Sustainability Green Manufacturing; KwaZulu Natal; UCTD; SDG-15: Life on land